LITHUANIAN-GERMAN RELATIONS IN THE SPHERE OF SECURITY DURING THE RUSSIAN-UKRAINIAN WAR IN 2022-2024 - MALUŻINAS Martinas (2024)
The concept of Lithuanian foreign policy is based on three basic priorities: membership in NATO, membership in the European Union and friendly relations with neighbors. The axiological basis for building international relations was based on values such as common attachment to democratic values, human rights and support for an international order based on rules, law and peace. Thirty-three years later, this Baltic country of about 2.8 million people is taking bold steps to counter Russia’s imperialist aspirations at a time of international security crisis. The aim of the article is to analyze the changing geopolitical reality through the strengthening cooperation between Germany and Lithuania in the area of security policy. The research problem of the work was defined in the form of a question: what are the characteristics of the issues of Lithuanian-German relations during the Russian-Ukrainian war in 2022-2024 In the context of potential threats generated by Russia? What will be the composition of the future German brigade in Lithuania and its preliminary schedule? The starting point of the discussion is the hypothesis that: small countries are able to start a process that can bring benefits to the entire region and thus contribute in their own way to building international peace and security. Moreover, Lithuania, by pursuing an active and effective foreign policy based not only on national but also regional interests, contributes in its own way to building international security; Moreover, tangible results are being achieved thanks to Lithuania’s efforts to attract Berlin’s attention and pressure it to take more decisive action against Ukraine and its eastern flank. The research method used in the work was content and content analysis and analysis of secondary data. The argument for taking up this issue is the lack of both Polish and English-language literature. For this reason, the presentation of preliminary research results provides a perspective for further, in-depth research on this topic.